Student Perceptions of Desired Learning Media Technology Development - Andayani; Suryo Prabowo; Abd Gafur; Robinson Situmorang; Bramianto Setiawan (JTP - Jurnal Teknologi Pendidikan, 2024)
This study aimed to explore the perceptions of undergraduate students on suitable learning media for website development. A qualitative method with a case study type was used in this research. Fifty undergraduate students from the Educational Technology department participated. A questionnaire was used as the instrument to gather data on the necessary learning media. Data analysis was performed using NVivo 12 software, and results were presented as percentages based on two indicators: technology accessibility and learning materials. The study’s results and discussion highlighted two crucial factors influencing the choice of learning media in website development education. First, technology accessibility factors, encompass technological support and interaction. Second, learning material factors, including the type and complexity of the material. These findings offer valuable insights for developing more effective learning media in web development courses by taking these key factors into account.